The Effect of Autogenic Relaxation on Blood Pressure Changes in Patients with Hypertension: Literature Review - Imamah, Indah Nur (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Hypertension is still the number one killer disease in Indonesia. Approximately one billion people worldwide suffer from this disease. Hypertension can be treated with pharmacological and non-pharmacological treatments. One of the non-pharmacological treatments is autogenic relaxation. This study aims to determine the effect of autogenic relaxation on hypertensive blood pressure changes. This study uses a Systematic Literature Review, a synthesis of systemic, precise, comprehensive literature studies by identifying, analyzing, evaluating through collecting existing data with an explicit search method and involving a critical review process in selecting the studies. The data from 11 journals were obtained from screening a number of journals from Science Direct, and Google Scholar. The results of the analysis showed that there was an effect of autogenic relaxation on blood pressure in hypertensive patients. Autogenic relaxation can benefit changes in blood pressure in hypertensive patients and is suitable if done regularly.